A symbology proposition for large-scale topographic mapping applied to the municipality of the city of Maputo - Comé, Sérgio; Sluter, Claúdia Robbi; Moiane, André Fenias (Seven Editora, 2023)
This article deals with a proposition of symbology for large-scale topographic mapping. Emphasis was given to the case of the Municipal City of Maputo and public and private institutions that operate in urban mapping. Of the five available topographic maps, visual analysis was carried out, based on legibility and visibility criteria previously proposed by other authors. For each class of features, the graphic primitives used in each card were identified and, in the evaluated sequence, the possibility of maintaining the graphic primitive or modifying its representation in the proposed symbology. In many cases, semantic and geometric generalization was necessary to fit the symbology. The research showed that the library of symbols proposed in table form can be applied in the topographic mapping of urban areas, provided that the precepts of cartographic language and theories of graphic semiology are observed in order not to compromise the process of cartographic communication. A proposition of symbology for large-scale topographic mapping requires the cartographer to comply with the rules and specification criteria for maintaining logical consistency between topographic maps of subsequent scales, such as maps of 1:25.000 and smaller that follow the norms established by CENACARTA. DOI:https://doi.org/10.56238/devopinterscie-253